Complying with the Kyoto Protocol under uncertainty: Taxes or tradable permits? - Philippe Quirion (Fondazione Eni Enrico Mattei (FEEM), 2002)
The Kyoto Protocol on climate change allocates tradable quotas to developed countries, but let them free to choose the means to respect their quota. There are good reasons for a country not to control its firms through internationally tradable permits. We thus compare a tax and purely domestic tradable permits for the European Union, the U.S and Japan. Information on abatement costs and international permit price is imperfect and stems from nine global models. Permits perform better than a tax for Japan and the U.S., whereas both instruments yield a similar outcome for Europe. Applying Weitzman (1974)'s framework in this new context, we show that these results are due to the positive correlation between costs and benefits: models that predict a low abatement cost in one country generally do so in others too, thereby forecasting a low international permit price.
Keywords: D81; Q25; Q28; 330; Climate change; Uncertainty; Policy choice; Umweltabkommen; Ökosteuer; Emissionshandel; Vergleich; USA; EU-Staaten; Japan